2020
DOI: 10.1155/2020/2487072
|View full text |Cite
|
Sign up to set email alerts
|

Combining Innovative Bioink and Low Cell Density for the Production of 3D-Bioprinted Cartilage Substitutes: A Pilot Study

Abstract: 3D bioprinting offers interesting opportunities for 3D tissue printing by providing living cells with appropriate scaffolds with a dedicated structure. Biological advances in bioinks are currently promising for cell encapsulation, particularly that of mesenchymal stem cells (MSCs). We present herein the development of cartilage implants by 3D bioprinting that deliver MSCs encapsulated in an original bioink at low concentration. 3D-bioprinted constructs (10×10×4 mm) were printed using alginate/gelatin/fibrinoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 93 publications
0
34
0
Order By: Relevance
“…A low MSC concentration was identified in healthy hyaline cartilage, indicating viable alternatives and the induction of chondrogenic genes by TGF-1. [80,81] Considering the importance of biomaterials' type and viscosity for 3D bioprinting of cell-laden bioinks, using a combination of gelatin, alginate, and fibrinogen was successful for cartilage 3D printing in the presence of a cocktail of BMP-2 and TGF-1 during a 56 day period. Gelatin and alginate have been previously applied as 3D systems to enhance the regeneration of hyaline-like cartilage tissue following the chondrogenic differentiation of MSCs within an ECM enriched in proteoglycans and type II collagen.…”
Section: Articular 3d Bioprinting Applying Stem Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…A low MSC concentration was identified in healthy hyaline cartilage, indicating viable alternatives and the induction of chondrogenic genes by TGF-1. [80,81] Considering the importance of biomaterials' type and viscosity for 3D bioprinting of cell-laden bioinks, using a combination of gelatin, alginate, and fibrinogen was successful for cartilage 3D printing in the presence of a cocktail of BMP-2 and TGF-1 during a 56 day period. Gelatin and alginate have been previously applied as 3D systems to enhance the regeneration of hyaline-like cartilage tissue following the chondrogenic differentiation of MSCs within an ECM enriched in proteoglycans and type II collagen.…”
Section: Articular 3d Bioprinting Applying Stem Cellsmentioning
confidence: 99%
“…To address this issue, researchers have engineered 3D-printed agarose hydrogels with tailored properties by means of nano silicate additives. [80,107,108] The mechanical test and the bright field images of NIH/3T3 cells indicated that not only the structural integrity and shape fidelity of the extrusion-based bioprinted nanocomposite, but also the metabolic activity and morphology of the cells could be tailored using different concentrations of nano silicate (Figure 3A,B). [109] Collagen, as a triple-helix protein and respect to its natural and biological origin, has found wide attraction for gelbased skeletal tissue regeneration.…”
Section: Materials and Biomaterials For 3d-printable Hydrogels For Bomentioning
confidence: 99%
“…A low cell density of MSC (1 million) is beneficial for the chondrogenic differentiation potential. [ 116 ] Tröndle et al. revealed that high cell density (25 × 10 6 ± 3 × 10 6 cells mL −1 ) is beneficial while bioprinting primary endothelial cells in the DoD technique.…”
Section: D Bioprinting Process Parameters and Their Effect On Cellulmentioning
confidence: 99%
“…The last important factor is the environment. Chondrogenic matrix synthesis is driven by growth factors [ 57 , 58 , 59 , 60 , 61 ], oxygen levels [ 62 , 63 , 64 , 65 , 66 ], maturation time [ 67 ], and mechanical stimuli, including dynamic compression and shear stress, to mimic the natural diarthrodial environment [ 68 , 69 , 70 , 71 , 72 , 73 ]. Classical TE usually produces homogenous constructs.…”
Section: Articular Cartilage Lesions and Their Surgical Treatmentmentioning
confidence: 99%
“…To further reproduce the calcified layer, calcium can be added to the bioink to increase the expression of hypertrophic cartilage markers [ 166 ]. To fine-tune the chondrogenesis of the embedded MSCs in 3D-printed constructs, the use of growth factors, especially TGF-β family members, is essential [ 60 ].…”
Section: Bioextrusion Processes For Cartilage Tissue Engineeringmentioning
confidence: 99%